Bio-geochemical evolution and critical element mineralization in the Cretaceous-Cenozoic coals from the southern Far East Russia and northeastern China. (June 2020) - Nechaev, Victor P.; Bechtel, Achim; Dai, Shifeng; Chekryzhov, Igor Yu; Pavlyutkin, Boris I.; Vysotskiy, Sergey V.; Ignatiev, Alexander V.; Velivetskaya, Tatiana A.; Guo, Wenmu; Tarasenko, Irina A.; Nechaeva, Evgeniya V.; French, David; et al.
Abstract: A total of 23 coal and two carbonaceous shale samples of the Early Cretaceous-Miocene, collected from different basins in the Primorye and Sakhalin regions of Russia, and the Hunchun basin of northeastern China, were used in this study for determination of major oxides (by AES and XRF), trace elements (by ICP-MS), sulfur, carbon, carbon isotopes, and major components of extractable organic matter (wet-chemical and gas-chromatographic analyses). Interpretation of the obtained data was intended to elucidate geodynamic and other geological processes controlling bio-geochemical compositions and critical element mineralization of the studied coals. The data suggest that inorganic matter in the studied coals was derived mainly from the Paleozoic granites and the Cenozoic felsic and intermediate tuffs. The Early Eocene and, in particular, Oligocene epochs represent the two major mineralization events in the regions, resulting in enrichment of Ge, W, Be, Mo, Sb, Sr, Ba, REY (rare earth elements and Y), Th, and U in the coals. The two events were related respectively to the Indo-Eurasian collision followed by plate reorganization in the Pacific and the opening of the Sea of Japan. The geodynamic changes were probably associated with mantle-derived volcanic activity and intensive degassing, which enhanced the capability of surficial and ground waters to leach and redistribute trace metals. Organic matter played a significant role in the system of mineralization, starting from weathering of source rocks and ending at the coal diagenetic stage. Organic acids significantly accelerated leaching and transportation of the metals, while they, together with sulfate-reducing bacteria, kerogen, alcohols + ketones, and n -alkanols in particular, played an important role in metal precipitation, mainly through reactions of cation exchange and adsorption. Highlights: Early Eocene and Oligocene geodynamic events are related to the coal mineralization. The mineralization included enrichment in Ge, W, Be, Mo, Sb, Sr, Ba, REY, Th, and U. Granite and felsic tuffs are major sources of inorganic matter in the coals. Acids, alcohols + ketones, and kerogen are associated with the mineralization. Sulfate-reducing bacteria accelerate the process of metal enrichment in coal.